2014
DOI: 10.1007/s10096-014-2095-x
|View full text |Cite|
|
Sign up to set email alerts
|

Increased risk of chronic fatigue syndrome following herpes zoster: a population-based study

Abstract: Chronic fatigue syndrome (CFS) is a complex disorder accompanied by unexplainable persistent fatigue, in which several etiological factors exist, such as viral infections. Using the National Health Insurance Research Database (NHIRD) of Taiwan, this study evaluated the association between herpes zoster (HZ) infection and the risk of CFS, and examined the possibility of patients developing postviral fatigue effects, including the possibility of developing other unexplainable chronic fatigue conditions. In this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…Numerous studies have suggested a potential role for HHV‐6 and/or EBV as triggers for ME/CFS and limited studies have suggested the involvement of VZV in ME/CFS . Conversely, there has only been a single study on GWI patients and herpesviruses suggesting that there was reactivation of multiple herpesviruses (HHV‐6, EBV, and VZV) in these patients .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have suggested a potential role for HHV‐6 and/or EBV as triggers for ME/CFS and limited studies have suggested the involvement of VZV in ME/CFS . Conversely, there has only been a single study on GWI patients and herpesviruses suggesting that there was reactivation of multiple herpesviruses (HHV‐6, EBV, and VZV) in these patients .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence from Taiwan and Japan suggests that patients with HZ are at increased subsequent risk of cardiovascular disease [546, 547], lymphoma [611] and other cancers [466, 612, 613], renal failure [614], SLE [615], multiple sclerosis [616], chronic fatigue syndrome [617], depression [618, 619] and erectile dysfunction [620]; however, the causality and significance of these associations remains unclear. Prevalent comorbidities such as metabolic syndrome disorders probably contribute to cardiovascular risk [547], while immunosuppression may underlie other conditions.…”
Section: Complicating Presentations and Disease Associationsmentioning
confidence: 99%
“…However, explicit psychiatric diagnoses, mood, and anxiety disorders have rarely been examined, except for depression, with HZ reported to be an independent risk factor for major depression and depressive disorders in a large prospective study [18]. In general, the relative effects of these risk factors for HZ onset decreased with increasing age [13].Interestingly, recent studies have reported that chronic cytomegalovirus (CMV) infection may stimulate increasing HZ virus reactivation with age [19], and that there is a significant increase in chronic fatigue after HZ, with incidence increasing over time [20]. It is impossible not to pose the critical question of whether chronic activation of inflammatory pathways plays a role in the pathogenesis of frailty [21].…”
mentioning
confidence: 99%
“…Interestingly, recent studies have reported that chronic cytomegalovirus (CMV) infection may stimulate increasing HZ virus reactivation with age [19], and that there is a significant increase in chronic fatigue after HZ, with incidence increasing over time [20]. It is impossible not to pose the critical question of whether chronic activation of inflammatory pathways plays a role in the pathogenesis of frailty [21].…”
mentioning
confidence: 99%